Mosquito Control Devices and Services for Florida Homeowners - C. Roxanne Rutledge-Connelly (EDIS, 2003)
There are many devices on the market advertised to control mosquitoes. The advertisements for these devices are aimed at the average homeowner. How do you know if they will work? It is unfortunate that many advertisements take advantage of the concerns we have to protect family members from mosquito-borne disease. This factsheet is provided to assist homeowners in smart decision-making when it comes to protecting the health of you and your family. This document is ENY-692, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: December 2003.